Performance evaluation of ejector based CO2 system for simultaneous heating and cooling application in an Indian dairy industry. (1st December 2020) - Dasi, Koti; Singh, Simarpreet; A.M., Guruchethan; Maiya, M.P.; Hafner, Armin; Banasiak, Krzysztof; Neksa, Petter
Highlights: Ejector based transcritical CO2 system for a dairy industry is analyzed with and without IHX. Experimental studies are carried out to validate the model. Energy and exergy analysis are carried out. COP and exergy efficiency are improved by 6.4% and 4.5% respectively with the addition of IHX. Abstract: India is ranked first in milk production, and its goal is to increase annual production to 300 million tons by 2024. The dairy industry requires multi-temperature cooling and simultaneous heating. In the present study, the ejector based transcritical CO2 system with two evaporators (LT at −10°C, MT at 0°C) is analyzed and proposed for fulfilling both cooling and heating demands in the dairy industry. Ejector based systems with and without internal heat exchanger are analyzed and compared. The effects of gas cooler outlet temperature, receiver pressure and gas cooler pressure on the performance of the system are investigated by energy and exergy analysis. The gas cooler pressure is analyzed for achieving the desired pasteurization temperature. The internal heat exchanger not only reduces the minimum gas cooler pressure required for the pasteurization temperature but also increases the system COP and exergy efficiency by 6.4% and 4.5% respectively. Second law analysis shows that the maximum exergy efficiency of the system is 38.4%.